Breech Presentation Among Nullipara at Term: An Indication for Caesarean Section - Dongol, A; Regmi, S; Manandhar, S; KC, S (Kathmandu University Medical Journal, 2014)
Background Breech is the commonest malpresentation. Vaginal breech delivery in a nulliparous lady carries higher risk than in multiparous ladies. Poor neonatal outcome following vaginal delivery has made the mode of delivery a matter of controversy. Objective To evaluate the outcome of planned caesarean section among nullipara ladies with breech presentation. Method This is a prospective, analytical study conducted in Dhulikhel Hospital Kathmandu University Hospital from January 2008 to June 2012 among 102 nullipara ladies at term gestation with breech presentation. All cases underwent caesarean section either elective or emergency. During section cause of breech presentation was searched for. Neonatal condition was evaluated using APGAR Score, need for resuscitation and admission in NICU. Post partum status was also recorded for evaluation of maternal morbidity and mortality. Results These Nullipara ladies often had some reason for breech presentation, the most common being cord around the neck. Perinatal outcome was uneventful in 97(95%) neonates, there were two (2%) still birth and three (3%) needed NICU care. APGAR was good in 92 neonates, average in eight and poor in two. Total 16(15.6%) ladies stayed hospital for more than eight days. Among them 11(10.7%) developed wound infection and five stayed in hospital waiting for baby. Conclusion Nullipara ladies with breech presentation should have elective caesarean section as a preferred route of delivery. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10998 Kathmandu Univ Med J 2012;10(4):66-69